2020
DOI: 10.1037/aca0000206
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between depression, self-reflection, brooding, and creative thinking in a psychiatric sample.

Abstract: Although symptoms of depression likely interfere with creative thinking, rates of mood disorders appear to be higher than average in creative samples. Previous research has shown that a possible link between depression and creativity might best be explained by self-reflection, defined as the tendency to ponder or contemplate information related to the self. However, previous findings are constrained by the use of nonclinical student samples and the inability to examine the role of specific diagnoses associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Therefore, in mental health counseling and interventions for college students, it is important to help them to transform cathartic negative thoughts and emotions into positive perceptions of the traumatic event in order to facilitate the occurrence of PTG. Further, deliberate rumination had a positive effect on college students' creativity (Verhaeghen et al, 2005(Verhaeghen et al, , 2014Forgeard et al, 2020). In past studies, self-efficacy and rumination were considered as important factors influencing individual physical and mental growth, with the former often representing a positive influence and the latter being associated with mental illness (Takagishi et al, 2013;Karabati et al, 2017;Nota and Coles, 2018), However, the two dimensions of rumination have not been comprehensively discussed.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in mental health counseling and interventions for college students, it is important to help them to transform cathartic negative thoughts and emotions into positive perceptions of the traumatic event in order to facilitate the occurrence of PTG. Further, deliberate rumination had a positive effect on college students' creativity (Verhaeghen et al, 2005(Verhaeghen et al, , 2014Forgeard et al, 2020). In past studies, self-efficacy and rumination were considered as important factors influencing individual physical and mental growth, with the former often representing a positive influence and the latter being associated with mental illness (Takagishi et al, 2013;Karabati et al, 2017;Nota and Coles, 2018), However, the two dimensions of rumination have not been comprehensively discussed.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Iterative rumination on individuals and events is also an important factor in the development of creativity (Verhaeghen et al, 2005). For example, it has been suggested that rumination contributes to the development of higher-value creative ideas (Forgeard et al, 2020). Self-reflective rumination stimulates interest in creative behavior (Verhaeghen et al, 2005(Verhaeghen et al, , 2014.…”
Section: The Moderating Role Of Deliberate Ruminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a study by Jamison et al (1980), people with bipolar disorder reported that their depression state led to a heightened sensitivity to their mood, which in turn had a positive effect on their creativity. Kaufmann (2015) and Forgeard et al (2020) have also found that negative mood was beneficial when identifying problems and evaluating ideas during creative thinking (for example, to measure the quality of one's ideas). Supported by such evidence, other scholars believed that the stimulative effect of depression state in the creative process was due to the increased introspection, which led to high sensitivity to internal content (Richards, 1981).…”
Section: Self-focused Attentionmentioning
confidence: 99%
“…Depression and rumination are closely related. Forgeard et al (2020) found that rumination can explain the relationship between depressive symptoms and the generation of more valuable ideas. This may be because the fact that the rumination made people set a high and strict standard for themselves, and people may use these same standards to produce thoughts.…”
Section: Introductionmentioning
confidence: 99%